Malignant Hyperthermia in Alpaca (Vicugna pacos) - Isaia Sampedro, Guida; Hamilton Nunes Soares, Renan; Lopes Simão, Beatriz; Ferreira Feyh, Mariana; Lourenço das Chagas, Nicole; Feser, Mariane; Müller da Silva, Taiara; Carolina Barreto Coelho, Ana (Acta Scientiae Veterinariae, 2025)
Background: Malignant hyperthermia (MH) is a metabolic myopathy that affects several species, including humans; it occurs because of a sudden increase in calcium in the muscle fibers in genetically susceptible individuals. In camelids, such as alpacas, it is related to heat stress, caused, for example, by an environment with high temperatures. However, there are no reports of MH in alpacas in Brazil. Herein, we aimed to describe the anatomopathological examination findings via necroscopy and histopathological analyses of 2 alpacas suffering from MH. Cases: A fertile, adult, female alpaca with white fur that was not shorn, presented with hyperthermia (42.6°C), prostration, tachypnea, and paresis on a day when the temperature recorded in Rio Grande do Sul was 38°C, which felt like 46°C. At the veterinary clinic, tylosin and dipyrone were administered intramuscularly; however, the animal died. Upon examination, a complete blood count revealed erythrocytosis, anisocytosis, leukocytosis because of neutrophilia and thrombocytopenia. Biochemical evaluation revealed an increase in aspartate aminotransferase (AST), creatine kinase (CK), creatinine, and urea levels. The following day, necroscopic examination revealed moderately congested mucous membranes in the ocular and oral cavities, very pale striated muscles, and a discreetly pale liver with accentuation in the lobular pattern. The lungs were heavily armed, with costal impressions and a shiny dark red-to-purple surface; the more depressed areas were black. There was a significant amount of a reddish and frothy liquid in regions of the trachea and bronchi. Microscopic evaluation of the lung revealed diffuse moderate-to-marked accumulation of amorphous eosinophilic material. Diffuse congestion and moderate and multifocal hemorrhages were noted in the subendocardial region of the heart. Skeletal muscle examination revealed a moderate-to-marked difference in the size of some muscle fibers, with degeneration and necrosis of cardiomyocytes, loss of angulation and flocculation, and edema between the muscle fibers. These fibers, severely damaged because of atrophy, had multinucleated cells. The difference in fiber content was moderate in other muscle fibers. In all muscle fibers, there was moderate edema between the fibers. The spleen and brain were congested. In the liver, mainly in the centrilobular areas, a brownish granular pigment was detected in the cytoplasm of hepatocytes. All gastric compartments demonstrated diffuse and marked autolysis. Another alpaca who was in contact with the female alpaca presented with similar clinical signs; however, they had a milder form. After the line of management was altered, the animal recovered. No other alpacas were afflicted. Discussion: To establish a diagnosis of MH, it is necessary to correlate epidemiological data and clinical history with macroscopic and histological lesions as well as hematological examination findings. The increase in CK and AST levels demonstrated muscle injury. The clinical signs of prostration, tachypnea, muscle rigidity, and hyperthermia, in addition to extremely pale striated skeletal muscles, were indicative of MH. Differential diagnoses of capture myopathy, lymphocytic myositis, selenium and vitamin E deficiency, or accidental Senna poisoning were discarded because of the history elicited and injuries detected. To the best of our knowledge, this is the 1st case report of MH in alpacas in Brazil. Our findings indicate that it is extremely important to instruct breeders regarding the management of animals in hot weather. Keywords: camelid, histopathology, muscle tissue, muscle necrosis. Título: Hipertermia Maligna em Alpaca (Vicugna pacos) Descritores: camelídeo, histopatologia, tecido muscular, necrose muscular.